2008
DOI: 10.1111/j.1467-9922.2008.00443.x
|View full text |Cite
|
Sign up to set email alerts
|

Age‐Related Differences in the Motivation of Learning English as a Foreign Language: Attitudes, Selves, and Motivated Learning Behavior

Abstract: Our study describes the motivation for learning English as a foreign language in three distinct learner populations: secondary school pupils, university students, and adult language learners. Questionnaire data were collected from 623 Hungarian students. The main factors affecting students' second language (L2) motivation were language learning attitudes and the Ideal L2 self, which provides empirical support for the main construct of the theory of the L2 Motivational Self-System (Dörnyei, 2005). Models of mot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

36
257
7
20

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 337 publications
(320 citation statements)
references
References 48 publications
36
257
7
20
Order By: Relevance
“…In many previous studies of motivation in second language acquisition it was found that another variable having an important influence on motivational factors is the age of learners of various languages in various countries (e.g., gömleksiz, 2001;MacIntyre et al, 2002;Donovan & MacIntyre, 2005;Figueiredo & Silva, 2008;kormos & Csizér, 2008;Wong, 2008). these findings are also confirmed in our study.…”
Section: Discussionmentioning
confidence: 99%
“…In many previous studies of motivation in second language acquisition it was found that another variable having an important influence on motivational factors is the age of learners of various languages in various countries (e.g., gömleksiz, 2001;MacIntyre et al, 2002;Donovan & MacIntyre, 2005;Figueiredo & Silva, 2008;kormos & Csizér, 2008;Wong, 2008). these findings are also confirmed in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Ezenkívül a 90-es években egyre intenzívebb kutatás indult el a nyelvtanulás sikerét meghatározó háttértényezők bevonásával, az életkor, a nemek közötti különbségek, a motiváció és az attitűdök hatásának elemzésével. A 2000-es évektől kezdve a vizsgálatok még intenzívebbé váltak, a nyelvtanulási stratégiák kapcsolatának elemzésére, a kognitív és affektív faktorok feltárására került a hangsúly (Kormos és Csizér, 2008, Zhang, Gu és Hu, 2008. Az utóbbi másfél évtizedben olyan újabb kutatási terület is kapcsolódott a nyelvtanulási stratégiákhoz, mint a metakogníció vagy az önszabályozott tanulás (Nikolov, 2003).…”
Section: A Nyelvtanulási Stratégiák Kutatása Több éVtizedes Múltra Teunclassified
“…That reason can have and integrative orientation or an instrumental one. An integrative attitude, initially associated with the learner's interest to identify with the target language community, seems to be an outdated concept in the globalized world of the twenty-first century (Kormos & Csizér, 2008). In turn, it is said to reflect a desire to learn about the language group and to meet people belonging to it.…”
Section: Teaching Goalsmentioning
confidence: 99%